Immature platelets and antiplatelet therapy response to aspirin in Kawasaki disease - Pi L; Che D; Long HF; Fang ZZ; Li JW; Lin SY; Liu YF; Li M; Bao LJ; Li W; Zhang Y; Deng QL; et al. (Dove Medical Press, 2018)
Lei Pi,1,* Di Che,1,* Haifeng Long,2,3,* Zhenzhen Fang,4 Jiawen Li,1 Shuyi Lin,2 Yunfeng Liu,2 Meiai Li,2 Lijuan Bao,2 Wenli Li,2 Yuan Zhang,2 Qiulian Deng,2 Techang Liu,5 Li Zhang,5 Xiaoqiong Gu1,2 1Department of Clinical Biological Resource Bank, Guangzhou Institute of Pediatrics, Guangzhou Women and Children’s Medical Center, Guangzhou Medical University, Guangzhou, China; 2Department of Clinical Laboratory, Guangzhou Women and Children’s Medical Center, Guangzhou Medical University, Guangzhou, China; 3Department of Clinical Laboratory, The First Clinical Medical College, Jinan University, Guangzhou, China; 4Program of Molecular Medicine, Guangzhou Women and Children’s Hospital, Zhongshan School of Medicine, Sun Yat-Sen University, Guangzhou, China; 5Department of Cardiology, Guangzhou Women and Children’s Medical Center, Guangzhou Medical University, Guangzhou, China *These authors contributed equally to this work Introduction: Kawasaki disease is a kind of systemic vasculitis that mainly damages moderate and small-sized blood vessels, and is a leading cause of coronary artery lesions (CAL). Antiplatelet therapy is a routine component of Kawasaki disease treatment strategies. So it is important to evaluate the antiplatelet effect of aspirin because of the individual biological variability of antiplatelet effect of aspirin. The immature platelet fraction (IPF) has attracted particular attention as it may influence the antiplatelet effect of aspirin. This study investigated the prognostic factors for evaluating the degree of vasculitis and the effect of antiplatelet therapy in children with Kawasaki disease. Materials and methods: Blood samples were collected from 44 patients with Kawasaki disease before aspirin treatment and 7 to 10 days after treatment. The IPF counts, percentage of the IPF, and highly fluorescent IPF were detected by a Sysmex XE-5000 instrument. The levels of 11-dehydrothromboxane B2 (11-DH-TXB2), soluble CD40 ligand (sCD40L), and soluble P-selectin (sP-selectin) were measured by ELISA. The correlation between the measured factors and the degree of coronary artery damage in Kawasaki disease was analyzed. Results: We found that 11-DH-TXB2, sP-selectin, and sCD40L levels were much more elevated in the CAL group than in the non-coronary artery lesions (NCAL) group before aspirin treatment. The concentrations of 11-DH-TXB2, sCD40L, sP-selectin, and IPF were reduced after aspirin treatment in the NCAL group but not the CAL group. This is related to the degree of coronary artery damage in Kawasaki disease patients. Additionally, 11-DH-TXB2, sCD40L, sP-selectin, and IPF were positively correlated with the degree of coronary artery damage in Kawasaki disease patients. Conclusion: The current study suggests that the presence of high plasma concentrations of 11-DH-TXB2, sCD40L, sP-selectin, and IPF can be considered a risk factor and experimental biomarker for CAL in Kawasaki disease patients. Keywords: Kawasaki disease, coronary artery lesions, aspirin, immature platelet fraction